ANALISIS STRATEGI PROMOSI DALAM MENINGKATKAN PENJUALAN RENDANG TELUR YOLANDA DI KOTA PAYAKUMBUH - Fadilla Putri; Sandra Dewi (CV. Adiba Aisha Amira, 2025)
The background of this study is to see the promotional strategy of rendang yolanda in increasing sales of rendang yolanda in the city of Payakumbuh. Which promotional strategy will have an impact on a business, both positive and negative impacts. The purpose of the study is to determine and analyze the promotional strategy to increase sales of rendang yolanda in the city of Payakumbuh. The research method used by the author here is qualitative research, with the key informant of this study being Mr. Nasrudin as the owner of rendang yolanda. In data collection, researchers used observation, interview, and documentation methods. The results of the study obtained from the analysis of promotional strategies in increasing sales of rendang egg yolanda in the city of Payakumbuh are that the promotional strategy used is quite good and runs well, where rendang yolanda has implemented a promotional mix in promoting its rendang egg. Using a promotional mix will make more people know rendang yolanda and increase sales of rendang yolanda. So that this can increase sales of rendang yolanda and increase profits.